Study of Cytotoxic Effect of Crude Extracts of Bidens Tripartita,Panex Ginseng,Ceylon Cinnamon and Citrullus Colocynthis on Mice Mammary Adenocarcinoma Cell line - Al-Naemi, H. A. Sh. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The cytotoxic effect of different concentrations of Crude extracts of Bidens tripartita , Panex ginseng , Ceylon cinnamon and Citrullus colocynthis on mice mammary adenocarcinoma cell line were studied . The concentration used were 125 , 250, 500, 1000 Microgram/militer . The exracts were prepared by using hot water method . The preliminary chemical tests revealed acidic pH of all extracts. The time of exposure used were 24, 48 and 72 hrs.The results showed a clear toxic effect of all extracts depending on the time of exposure and the dose . The Ceylon cinnamon had the highest effect on adenocarcinoma 87.33% , followed by Bidens tripartita 86.79%, Citrullus colocynthis 74.39% and the lowest effect was by Panex ginseng extract 70.71%.